SENSE OF LOSS IN THE EYES OF THE TERTIARY STUDENTS - Castante, Riezel Dumagpi; Beluso, Nenita; Vasques, Michael (IDEAS: Journal of Management & Technology, 2025)
The sense of loss is a universal human condition which does not exclude anyone regardless of demographics and societal roles. Despite numerous investigations with the sense of loss, there remains a gap in higher education institutions (HEIs) locally. Hence, this study attempted to explore the sense of loss among a purposive sampled tertiary students encompassing their academic, personal, and social life utilizing a phenomenological approach. Through interviews vis-à-vis the use of a validated semi-structured questionnaire with open-ended questions, the experiences of the participants were gathered, transcribed, thematically analyzed, and interpreted. Results of the study revealed the experiences which constitute the sense of loss are death, brokenness, rejection, and separation; the impact of loss in the participants’ academic life is brought about by lack of focus and interest, however a positive pursuit to education became apparent; given the negative disposition that is evident, there was a positive disposition among the participants despite the impact of loss in their personal life; in terms of the impact of loss to the participants’ social life, the occurrence of isolation and alienation surfaced, however, self-direction and support system emerged in the captured essences from the participants’ experiences; and, a simulacrum of the sense of loss among college students was developed. It is recommended that a supportive school mechanism be established through institutional services and programs juxtaposed with the sensitivity to issues of loss be manifested during curricular engagement. Further investigations should consider variances in research approaches to improve the understanding surrounding the phenomenon of loss.